Production of antifungal compounds by Bacillus spp. isolates and its capacity for controlling citrus black spot under field conditions - Kupper, Katia Cristina; Moretto, Rafael Kupper; Fujimoto, Andreia [UNESP] (Springer, 2019)
Orange juice is a major agricultural product, and oranges are among the most widely sold fresh fruits in several countries. Citrus black spot (CBS), caused by the fungus Phyllosticta citricarpa, affects almost every species of citrus, causing a esthetic depreciation of the fruit and fruit drop, with consequent financial loss for its in natura commercialization. Fungicides are the major control measure for CBS, but have limited efficiency and high cost, and give rise to fungal strains resistant to these products. This work assayed the production of antifungal compounds by Bacillus spp. isolates and tested the potential of two isolates from B. subtilis (ACB-AP3 and ACB-83) for controlling CBS under field conditions with two previously untested orange varieties. A total of 15 isolates produced cell-free, thermostable or volatile compounds effective in suppressing P. citricarpa growth in vitro. It was possible to detect the production of two antibiotics (iturin and surfactin) by B. subtilis ACB-83. Additionally, B. subtilis isolates ACB-AP3 and ACB-83 displayed significant effects in controlling the disease under field conditions.
Keywords: Citrus sinensis; Phyllosticta citricarpa; Volatile; Thermostable; Cell-free antifungal compounds; Liquid chromatography; Mass spectrometry